Hospitalization Due to Assault Injury Across Different Age Groups, 2010 to 2014: A Population-Based Study in New South Wales, Australia. (January 2019) - Seah, Rebecca; Draper, Brian; Mitchell, Rebecca
Objective. Assault is a global public health issue that affects individuals of all ages. This study describes the epidemiological profile of assault-related hospitalization and health outcomes across different age groups in New South Wales, Australia. Methods. Population-based linked hospitalization and mortality data from January 1, 2010, to June 30, 2014, were used to identify assault-related hospitalizations. Age-standardized rates were calculated and health outcomes were examined by age group. Results. There were 22 579 hospitalizations due to assault, with an age-standardized rate of 55.9 per 100 000 population (95% confidence interval = 55.2 to 56.70). Assault by bodily force (63.1%) and by sharp or blunt objects (21.6%) were the most common injury mechanisms. Individuals above 60 years had the highest mean hospital length of stay at 7.3 days, 30- and 90-day mortality, and average hospitalization costs at $9757. Conclusion. The findings have important implications in informing the development and strategies to reduce assault-related incidents in the community.